2019
DOI: 10.31413/nativa.v7i6.7835
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica Da Florística E Da Estrutura Horizontal Em Um Fragmento De Floresta Ombrófila Mista Montana

Abstract: Este trabalho objetivou analisar as alterações na composição florística e estrutura horizontal em um fragmento de Floresta Ombrófila Mista, localizado na Floresta Nacional (FLONA) de Irati, Paraná, Brasil, assim como compará-lo quanto à florística e estrutura de outros fragmentos florestais localizados em FLONAs da região sul do país. Todos os indivíduos com diâmetro à altura do peito maior ou igual a 10 cm (DAP ≥ 10 cm) foram identificados e mensurados ao longo de nove anos. A floresta apresentou elevada riqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…As for the specific richness of the botanical families, it was found that the most frequent families observed together had approximately half of the species observed. The leadership of the families Myrtaceae, Lauraceae, Fabaceae, Salicaceae, and Rubiaceae in the tree composition agrees with the studies conducted in this forest typology in many localities [51,52,55,56,58,59,61,63,[68][69][70]72,73].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As for the specific richness of the botanical families, it was found that the most frequent families observed together had approximately half of the species observed. The leadership of the families Myrtaceae, Lauraceae, Fabaceae, Salicaceae, and Rubiaceae in the tree composition agrees with the studies conducted in this forest typology in many localities [51,52,55,56,58,59,61,63,[68][69][70]72,73].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the horizontal structure, we found tree densities that are many times higher than in other MOF remnants located in protected areas, such as the "Parque Estadual das Araucárias" (SC, Brazil), with a density of 1368 trees ha −1 [64], and in FLONA (Irati, PR) with 567 trees ha −1 [63] and 561 trees ha −1 [59]. However, the basal area of the studied urban forests was smaller than that observed in the FLONA in São Francisco de Paula (RS, Brazil; 79.05 m 2 ha −1 ), although the density of 1445 trees ha −1 was smaller than that observed in the studied remnants [55].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The maximum growth series of some jaboticaba trees reached over 100 years of age (see Table 1) at DBH (1.30 m above ground level), in CH, PB, and VT. As these are locations with a high density of the species (> 40 trees ha -1 ), instead in Irati, other region of Paraná, the density was 1.56 jaboticaba trees ha -1 (Roik et al, 2019), this may indicate anthropogenic intervention in establishing these populations. The influence of indigenous people leading to more spread and density of useful and edible fruit species in Brazil has been recently demonstrated (Andrade et al, 2019;Caetano-Andrade et al, 2020;Cruz et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the stands are in a temperate climate with mild summer, subtropical wet season, uniform precipitation and an average temperature of 22ºC, and average annual precipitation of 1605,7 mm with frequent frosts (IBGE, 2021;SIMEPAR, 2021). The native cover in the area is a Mixed Ombrophilous Montane Forest also known as Araucaria forest (Roik et al, 2019).…”
Section: Study Areamentioning
confidence: 99%